DIMENSI KEARIFAN LOKAL SASTRA LISAN TERNATE DALAM PERSPEKTIF FILSAFAT KEBUDAYAAN - , Syahyunan Pora, S.Fil, Dr. M. Mukhtasar Syamsuddin ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Research titled Dimension of Local Wisdom Oral Literature of Ternate in the Perspective of philosophy of culture actually based on the permissive culture of Indonesia in an era of globalization. Besides the low appreciation of local cultural values that exist. The purpose of this research to reveal the value of local wisdom contained in the oral literature of Ternate as part of the cultural artifacts that actually contains the philosophical values. The value of local wisdom represented in the oral literature of Ternate is expected to be a solution to the development and challenges of these era that are increasingly dynamic and complex. This research is a library research that uses hermeneutics and heuristic methods. The object of the material in this research are oral traditions and oral literature of Ternate, whereas formal objects that are used as analytical tools is a philosophy of culture. methodical study of elements used are description, historical, abstraction and heuristics. The results obtained in this study were: first: the oral literature of Ternate, as part of a cultural artifact of philosophy. Second: correlation of oral literature of Ternate with a researched approach to formal object has the value local wisdom through traditions, customs prevailing in the local community. Third: Appreciation of human values and nature (environment). including an appreciation of the Creator through local knowledge of local communities, which in fact implies a world view or philosophy of life for the People of Ternate called philosophy "Jou Ngofangare". Fourth: the Philosophical Approach of culture as an object of formal research has a "red thread" alignment between the value of local wisdom with the values contained in the oral literature of Ternate. The relevance of this research can provide a sense of local knowledge for the public to the concept of cultural values according to the perspective of philosophy. Besides, local wisdom contained in the oral literature of Ternate were part of the philosophy of human culture that is more humanize. the harmony of Nature and the Creator is a unity that can not be separated. As reflected in the cultural wisdom of the nation's outlook on Indonesian way of life with the concept of Pancasila is "Bhineka Tunggal Ika" as part of the value of local knowledge of Indonesia which has been deeply rooted in Indonesian culture. through a long process as a tradition and culture, which until now has been a philosophy and world view of Indonesia.